2017
DOI: 10.1080/13880209.2017.1285326
|View full text |Cite
|
Sign up to set email alerts
|

Anti - Helicobacter pylori and antiulcerogenic activity of Aframomum pruinosum seeds on indomethacin-induced gastric ulcer in rats

Abstract: Context: Peptic ulcer is one of the most common diseases affecting mankind. Although there are many products used for its treatment, most of these products produce severe adverse reactions requiring the search for novel compounds. Some Afromomum species are used traditionally to cure acute gastritis.Objective: To evaluate the antiulcer activity of the methanol extract of Aframomum pruinosum Gagnepain (Zingiberaceae) seeds against two major etiologic agents of peptic ulcer disease; Helicobacter pylori and non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 43 publications
(45 reference statements)
0
7
0
2
Order By: Relevance
“…The inoculated culture media were incubated at 37 °C under microaerophilic conditions (CampyGen gas pack) for 7 days. Isolates that exhibited Gram negative curved rods on Gram stain reaction and were positive for catalase, oxidase and urease tests were considered as H. pylori [27, 28]. Confirmed isolates were suspended in eppendorf tubes containing Brain Heart Infusion broth supplemented with 5% horse serum (BHI-serum) with 30% glycerol and stored at − 80 °C until future use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculated culture media were incubated at 37 °C under microaerophilic conditions (CampyGen gas pack) for 7 days. Isolates that exhibited Gram negative curved rods on Gram stain reaction and were positive for catalase, oxidase and urease tests were considered as H. pylori [27, 28]. Confirmed isolates were suspended in eppendorf tubes containing Brain Heart Infusion broth supplemented with 5% horse serum (BHI-serum) with 30% glycerol and stored at − 80 °C until future use.…”
Section: Methodsmentioning
confidence: 99%
“…Subcultures were incubated at 37 °C under microaerophilic conditions (CampyGen gas pack) for 3 days and for two passages to ensure reliable growth. Gram staining, rapid urease and the catalase/oxydase tests were performed to confirm the identification [28, 29].…”
Section: Methodsmentioning
confidence: 99%
“…and even other species from the Aframomun genus, are traditionally used in Cameroon to cure gastritis. A methanolic extract from A. pruinosum seeds (125, 250 and 500 mg/kg) was evaluated as antiulcerogenic agent using two different models, NSAID- and H. pylori -induced gastric lesion in rats [ 113 ]. This study concluded that the extract from this plant possessed a moderate anti- Helicobacter and antiulcer activities, with a cytoprotective action due to the increase in mucus production stimulated by the endogenous prostaglandins and nitric oxide generation mechanisms [ 113 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…In recent years, Chinese herbal medicine has been shown to exhibit bacteriostatic effects on H. pylori [17]. Chang et al found that geniposide, a bioactive extract of Gardenia, could obviously reduce H. pylori infections by interfering with the growth and virulence as well as attenuating the inflammatory response [18].…”
Section: Discussionmentioning
confidence: 99%